Crime and Jews in Late Thirteenth-Century England: Some Cases and Comments - Rokéaḥ, Zefira Entin (Hebrew Union College annual / Jewish Institute of Religion, 1984)
The abundant and largely unpublished court records of late thirteenth-century England contain many references to Jews, whether as victims or perpetrators of crime, as bystanders, or as those on the periphery of crime. Not only were numerous Jews recorded in these scrolls as having been killed, robbed or assaulted by Christians; Jews were also the victims of their fellow Jews. Furthermore, Jews were accused of committing homicide, theft, robbery, assault, coinage violations, and (in one instance) rape — with Christians as their victims. In several cases of particular interest, Jews and Christians were partners in committing crime. The reporting of these cases — with the significant exception of the coinage violation cases of 1278-1279 — does not indicate anti-Semitic motives of the accusers or of the courts to any meaningful extent, while the patterns of Jewish involvement in crime seem similar to those of contemporary Christians in these records, which shed new light on the life of English Jewry in the years before the Expulsion of 1290, the first national and long-term expulsion of Jews in medieval Europe